(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
The former conflict around reading control has revived. Several questions have surfaced not only about the content of the works, but the relevance of the reading diary as well as the usefulness of the reading control tests. The questionnaire of the compulsory reading and the exercises of the reading control helped me create a new method. The IKON-method (Interaktív és Kreatív Olvasmányellenőrzés Napjainkban = Interactive and Creative Reading Control Today) integrates mainly the infocommunication technology into the flow of reading control. The main target of this paper is to direct the readers’ attention to the questions of reading control, and update the problem using the raised method, and help a professional discourse on the topic.